2011
DOI: 10.1159/000332984
|View full text |Cite
|
Sign up to set email alerts
|

Use of Probiotics in Abdominal Surgery

Abstract: Several clinical trials have demonstrated that the use of probiotics and synbiotics in patients undergoing abdominal surgery might be beneficial in preventing postoperative infectious complications. However, other investigators report that there is no evidence supporting any benefits from preoperative use of pre- and probiotics (synbiotics) in patients undergoing elective abdominal surgery, and that in some cases there is even an increased risk of mortality. Possible explanations behind these controversies may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Several studies have evaluated the effect of synbiotic treatment in preventing bacterial translocation under stressful conditions. An earlier study reported that perioperative synbiotic treatment prevented postoperative infectious complications after major hepatectomy for biliary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the effect of synbiotic treatment in preventing bacterial translocation under stressful conditions. An earlier study reported that perioperative synbiotic treatment prevented postoperative infectious complications after major hepatectomy for biliary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale clinical trials have already demonstrated several protective effects of probiotics or microbiome transplantation in combating intestinal infections, especially in managing secondary pathogens, such as Clostridium difficile [46–50] . These treatments have been shown to modulate host immune status and improve host resistance to pathogens [51,52] , and have also been applied to the treatment of tooth [53] , urinary tract [54] and vaginal infections [55] .…”
Section: Restoration Of the Pharyngeal Microbiomementioning
confidence: 99%
“…(33) Therefore, the effects of preoperative synbiotic treatments cannot be generalized and further studies are necessary to elucidate the role of synbiotic treatments on the rate of infection. (34,35) Recent meta-analyses demonstrated that preoperative synbiotic treatment decreased the rate of postoperative infections in general surgery. (36)(37)(38)(39) Over 30 papers included in these meta-analyses used Lactobacillus and/or Bifidobacterium as probiotics.…”
Section: Discussionmentioning
confidence: 99%